The Effect of Brand Image And Quality Of Educational Services On Customer Satisfaction - Connie Chairunnisa (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2018)
This study aims to provide information on the influence of brand image, the quality of education services on consumer satisfaction. This research uses survey method with path analysis technique, with a sample of 244 respondents. The results of the study prove that (1) there is a positive and significant influence between brand image on customer satisfaction, by 66.7% (2) there is a positive and significant influence between the quality of education services on customer satisfaction by 71.4% (3) there positive and significant influence between brand image and education service quality on customer satisfaction by 78.1%. In order to encourage the level of customer satisfaction, the Faculty needs to pay attention to the expectations and complaints of its customers, and continue to improve the quality of education services.